Optimalisasi Pengelolaan Pendidikan Inklusif - Elis Lisyawati; Nur Halimah; Khairunnisa Khairunnisa; Agus Mulyanto (EduInovasi: Journal of Basic Educational Studies, 2024)
Every Indonesian citizen has the right to a quality education as mandated in the 1945 Constitution Article 31 Paragraph 1. This right is inclusive and includes all citizens, including those with physical, emotional, mental and social disabilities. in an effort to maximize the management of inclusive education, School of Universe (SOU) develops various supporting components of inclusive education namely student management, inclusive curriculum development, management of education personnel, equipping facilities and infrastructure that support the learning process, management of financing and environmental management that involves the community. The method used in this research is a qualitative method with a descriptive approach. Data sources come from interviews, observations and documents. While the data analysis process refers to systematic steps based on analysis techniques ranging from data reduction, data display to drawing a conclusion through theme analysis. This research shows that School Of Universe (SOU) is able to manage Inclusive Education optimally. This success is achieved through the existence of a therapy and consultation center, namely the Learning Support Center (LSC) and the existence of a Research and Development (R&D) institution as a manager of students, staff and school educators. thus, SOU can provide appropriate, sustainable, and integrated services to develop inclusive education.